Digital Experience and Reuse Intention in Online Food Delivery Platforms - Nugroho, Aditiya Pratama; Nizar Fauzan; Setiawan, Aprilian Dani Bagus; Pratiwi, Arshanda (Journal of Digital Marketing and Halal Industry, 2025)
This study explores the determinants influencing the reuse intention of the GrabFood application among Generation Z consumers in Semarang City, Indonesia. Amid the rapid growth of online food delivery services, understanding the behavioral drivers of digital-native consumers remains underexplored, particularly in the context of Southeast Asian markets. This research contributes to the literature by integrating constructs from the Technology Acceptance Model (TAM) with marketing perspectives such as brand personality and promotional incentives, offering a comprehensive framework to examine user retention behavior. Utilizing a quantitative approach, data were collected from 210 Gen Z respondents through structured questionnaires employing a 7-point Likert scale. The analytical method employed was Structural Equation Modeling using Partial Least Squares (SEM-PLS), enabling robust assessment of the measurement and structural models. The findings reveal that brand personality, perceived usefulness, and voucher discounts significantly influence reuse intention, whereas perceived ease of use does not exhibit a direct effect. These results suggest that while functionality matters, emotional brand connections and tangible value propositions (such as discounts) are more salient in driving continued app usage among Gen Z users. The study offers practical implications for marketers and digital platform providers, highlighting the importance of aligning brand attributes with generational preferences and emphasizing value-driven promotions to enhance customer loyalty and sustained engagements.